Enhancing sengon seedling’s growth by using indigenous arbuscular mycorrhiza from tropical peatland - Tri Wira Yuwati; Atinah Atinah; Witiyasti Imaningsih (Jurnal GALAM, 2021)
The research aimed to determine the effect of arbuscular mycorrhizal isolates from Central Kalimantan peat swamp forest on the growth of Paraserianthes falcatharia. Arbuscular mycorrhizal isolates consisted of Glomus sp.2 (blackish brown) & Glomus sp.3 (dark brown) isolated from the peatland of Central Kalimantan. The mycorrhizal colonization was observed and plant growth parameters were measured for five months. The design used in this research was a complete randomized design and divided into Glo1S2 (Glomus sp.2, 2 spores), Glo1S4 (Glomus sp.2, 4 spores), Glo2S2 (Glomus sp.3, 2 spores), Glo2S4 (Glomus sp.3, 4 spores), control I and control II. The result showed that arbuscular mycorrhiza colonization significantly different between the treatment of inoculation compared with control. Glo2S4 treatment gave a significant effect on the growth of P. falcatharia in terms of plant height, stem diameter, number of leaves, root length and total biomass.